PLANNING OF FLY TRAP FOR TEMPORARY DOMESTIC WASTE IN HOSPITAL TO REDUCE THE INTENSITY OF FLY - Subagyo, Agistya Rizza; Salsabilla, Vionna Chantika; Samantha, Irma Juliana; Irham, Muhammad Faisal; Rapika, Muhammad; Sari, Mega Mutiara; Suryawan, I Wayan Koko (Journal of Environmental Engineering and Sustainable Technology, 2023)
Crowds of flies will add to the burden of everyday life. Moreover, if the flies try to eat the fly, they will be caught in the trap placed in the container's open mouth. Therefore, the fly population at X Hospital, Tulung Agung, should be controlled to a non-hazardous extent. This study analyzes the practical design for catching flies in the temporary hospital waste collection area. Fly traps are designed based on design criteria. Where fly traps can be made of wood and wire mesh to form a cylinder, inside which the flytrap is placed cone-shaped wire mesh. The fly trap, which has a length of 165 cm, a width of 180 cm, and a height of 30 cm, will be applied in a closed container with a capacity of 6 m3 and dimensions of 3.3 meters in length, 1.8 meters in width and 1.2 meters in height. This eco-friendly fly trap is made using perforated anti-mosquito wire mesh and arranged on top of the container. At the same time, the flies obtained can be used according to the needs that will be used.